(untitled) (International Journal of Language, Literacy and Translation, 2019)
The purpose of this study was to investigate the types and characteristics of collocations and semantic prosody of the collocations in Thai political news headlines in the Bangkok Post. The collocations were analysed to determine their types and characteristics and the types of semantic prosody and to find out whether the types of semantic prosody were affected by the news' context. In this study, 148 front-page political news headlines from January 1st to December 31st, 2015 from the Bangkok Post newspaper were selected for data collection. As a result, there were 271 collocations appearing in the political news headlines. Lexical collocations were often found in the news headlines. Nouns, verbs and adjectives are content words that convey lexical meaning for telling news stories in headlines. For the types of semantic prosody, negative semantic prosody was frequently found in collocations to call attention from readers. A small number of collocations changed their collocational meanings when they appeared in the news context. Attitudes and perspectives of the writers directly affected the language use for news writing and convey different meanings. The study revealed that the political news writers of the Bangkok Post were inclined to use lexical collocations more than grammatical collocations and had negative views in writing political news headlines.